Encyclopedia of virtual communities and technologies - Dasgupta, Subhasish, 1966- (Hershey, PA : Idea Group Reference, 2006)
This encyclopedia of virtual communities and technologies provides a much needed integrated overview of all the critical concepts, technologies and issues in the area of virtual communities--Provided by publisher
Includes bibliographical references and indexes
Keywords: Electronic villages (Computer networks) -- Encyclopedias; Telecommunication -- Encyclopedias; Virtual reality -- Encyclopedias